“Take Off 4-Health”: Nutrition Education Curriculum for a Healthy Lifestyle Camp for Overweight Youth - Harris, Nancy G.; Dunn, Carolyn Kusbit; Kolasa, Kathryn M.; Crawford, Yancey; Henes, Sarah T.; Kinner, Stephanie; Sutton, Virginia; Colby, Sarah E.; Collier, David N. (East Carolina University, 2010)
There is evidence that residential summer weight loss camps can be effective to initiate or support the small change approach to address childhood obesity. This report describes the development and evaluation of nutrition education for overweight adolescents attending a three week healthy lifestyle camp. Campers were given a diet prescription based on MyPryamid and self-selected their meals and snacks that were served family style. The curriculum included eating strategies known to contribute to healthy weight in youth. Campers demonstrated improved ability to estimate portion sizes. Thirty-four campers completed the three week experience with a weight loss considered to be safe. Note: the deposited item is not the final published version, but rather is the last revised manuscript sent to the publisher.
Keywords: Childhood obesity; Residential weight loss camps; MyPyramid